(untitled) (Research, Society and Development, 2022)
This prospective study aims to quantify patent documents and related technologies on fish edible coating, in the Espacenet database. The searches were carried out in April 2021, in the Espacenet database. From the integral results obtained, the terms "edible coating", fish and antimicrobial were combined, followed by an integrative AND connective between the words, for subsequent selection of the appropriate CIP, where a new search was performed using the "advanced search" field, incorporating the CIP and related terms. The analysis through the general scope table allowed selecting the code A23P20/10, which refers to coating with edible coatings, forming the search term "edible coating" AND fish AND A23P20/10. Twenty-nine documents were selected, six of which dealt directly with fish and its coating, distributed in the years 1998 (2), 1999 (1), 2005 (1), 2009 (1) and 2011 (1), being, therefore, 23 of the records obtained, referring to related technologies. The largest patent holder was the USA, with seven patents. Among the total documents evaluated, companies requested 66%.